ANÁLISE CONJUNTA BASEADA EM ESCOLHAS: UM ENFOQUE VIA MODELO LINEAR GENERALIZADO DE POISSON - BARBOSA, Eduardo Campana; SILVA, Carlos Henrique Osório; NASCIMENTO, Moysés; LÚCIA, Suzana Maria Della; MINIM, Valéria Paula Rodrigues (Brazilian Journal of Biometrics, 2017)
This paper presented a practical application of the choice-based conjoint analysis methodology. It was proposed the generalized linear Poisson model to analyze the data. The study was conducted with choices regarding the evaluation done by 144 consumers, eight samples of light yoghurt strawberry flavor, varying the information of three ingredients (sugar, fat and protein) in a full factorial design. Inferences and results are presented in terms of estimating the main effect of the attributes, probability and ratio of choice. It was found that the generalized linear Poisson model was equivalent to the multinomial logit model and can be used for the analysis in question. Practical results: the most likely choice was associated with yoghurt containing strawberry flavor light information: 0% of sugar, 0% fat and enriched with bioactive proteins.